Personal and environmental stress indicators experienced by pre-primary teacher trainees undergoing distance learning programmes (2010)
The study sought to explain the level of stress among pre-school teachers undergoing Open Distance Learning programmes at Universities of Ibadan, Lagos, Abia State University, and National Teachers Institute from different locations (Enugu, Akure, Ibadan, Lagos) using eight personal and environmental variables: gender, age; marital status; status at work; employment type; locus of control; and attitude towards distance education. Survey research type was used. Four valid and reliable instruments and Focus Group Discussion (FGD) were used to collect data on the relevant variables from 360 pre-school teachers undergoing distance learning programme in the universities. Data analysis involved using content analysis on the views of the respondents and stepwise multiple regression to examine the relationship between the stress level among distance education students and the eight independent variables. The results showed that the prevailing stressors as identified by ODL students (pre-school) include those of finance, ICT, emotional and course delivery channels. It also showed that the personal and environmental variables, when taken together, would effectively predict stress level among distance education students (R Adjusted = 0.6852; significant at 0.01 level); and that marital status is the most potent contributor to the prediction (T.ratio = 3.682; significant at 0.05 level). There is therefore need for ODL organizers to endeavour to evaluate antecedent conditions before embarking on new programmes. Thus, university authorities should organise attitude corrective workshops as part of the orientation activities for new students of distance education programme.